Tinjauan Literature tentang Knowledge Management: Definisi Konseptual, Dasar Teoritik dan Praktik Knowledge Management, serta Perkembangan Penelitiannya dalam Bidang Ilmu Manajemen dan Pendidikan - M. Shohibul Aziz (Intizam, Jurnal Manajemen Pendidikan Islam, 2020)
The main goal of this paper is to perform in-depth theoretical review and analysis the fields of knowledge management (KM) and explore development about KM in management literature, including trend in educational context. To address these purposes, first, we analyze and summerize few theoretical basis about KM which include definitions, stages about KM and theoretical foundation, and its evolution as well; second, we conduct a comprehensive review about the major approaches to design the KM system from different perspectives including knowledge representation and organization, knowledge sharing and performance measure for KM; third, we identify KM research trend in management and education studies